Large ventricular aneurysms occurring after myocardial infarction. Issue 5 (May 1978) - Letac, B; Leroux, G; Cribier, A; Soyer, R
Abstract : We have studied 33 patients with a large ventricular aneurysm complicating an anterior myocardial infarction. The features of myocardial infarction progressing towards an aneurysm were no previous history of coronary disease, severe infarction as shown by the severity of pain and the presence of pericardial rub and heart failure, and large increase in serum levels of cardiac enzymes. A large aneurysm usually follows a large infarction resulting from the total or partial occlusion of the left anterior descending artery, which is involved alone in about half the patients and is associated with lesions of the circumflex and right coronary arteries in the other half. In most cases, standard radiography showed an abnormal cardiac configuration, but in 7 patients (21%) there was no radiological evidence of aneurysm. ST segment elevation (mean 2.7 mm) was reported in all subjects but one. Heart failure was present in most patients and was an indication for surgical treatment in one-third of the patients. A large aneurysm was not a contraindication to operation even when at angiography the aneurysm seemed to occupy almost all the left ventricle. Twenty-one patients were operated upon for resection of the aneurysm with a mortality rate of 14 per cent.